Value Added: Technique for Corporate Performance Measurement under Social Perspective - Sahoo, Bharata Bhusan; Pramanik, Alok Kumar (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
Financial Analysts consider as profit the most important measure of business performance. Profit may be expressed in terms of money value and measured as sales margin percentage or be calculated as return of investment. These, in any form, are used as basis for measure of business performance. In recent years, considerable interest haveÂ been shown in the use of value added as an alternative or additional approach to measure the operational efficiency and profitability of a business. A lot of discussion have been going on about reporting the performance of an organization in terms of value added rather than conventional profit or loss. The information disclosed by the Statement of Value Added, based on Value Added Accounting and reporting is considered to be much more useful than that disclosed by the conventional profit and loss account in providing a realistic basis for measuring the economic performance of an organization. The concept has received great attention in accounting practices with the emergence of large corporations having significant bearing on the society and finally on the economy for multi-dimensional impact over and above the owners. Value added system is a very useful measure of judging the performance of an enterprise for managerial decision-making and for inter-firm comparison.Keywords: Value Added; Value Added Accounting and Reporting, Value Added Statement, Annual Report.